Can Chaos Explain Tragic Fate? Othello and Oedipus Rex Revisited - Ardana, Stefanus Galang (Lingua Susastra, 2025)
This paper employs chaos theory to analyze Shakespeare's Othello and Sophocles' Oedipus Rex, contrasting traditional interpretations of tragedy with the insights offered by chaos theory. Challenging analyses based on tragic flaws, this study reveals how minor initial deviations—Iago's manipulations in Othello and the priestly vagueness in Oedipus Rex—generate cascading feedback loops leading to catastrophic outcomes. Utilizing Prigogine's theory of bifurcation and Paulson's information theory, the paper traces how ambivalent or incomplete information triggers these trajectories, identifying pivotal bifurcation points like the handkerchief in Othello and the Shepherd's revelation in Oedipus Rex. While Othello's conclusion shows systemic collapse, Oedipus Rex demonstrates a form of reorganization. This approach uniquely contributes to literary studies by challenging linear causality and illustrating how meaning emerges unpredictably from instability within structurally chaotic tragic systems, particularly offering a rigorous examination of Oedipus Rex through the lens of chaos theory, a novel approach in existing scholarship. The study demonstrates that tragedy in these plays is not merely about disorder but a system governed by it, where causality is nonlinear and indeterminate.